Inorganic polyphosphate and polyphosphate kinase: their novel biological functions and applications - Shiba, T; Tsutsumi, K; Ishige, K; Noguchi, T (Biochemistry (Moscow), 2000)
In this review, we discuss the following two subjects: 1) the physiological function of polyphosphate (poly(P)) as a regulatory factor for gene expression in Escherichia coli, and 2) novel functions of E. coli polyphosphate kinase (PPK) and their applications. With regard to the first subject, it has been shown that E. coli cells in which yeast exopolyphosphatase (poly(P)ase), PPX1, was overproduced reduced resistance to H2O2 and heat shock as did a mutant whose polyphosphate kinase gene is disrupted. Sensitivity to H2O2 and heat shock evinced by cells that overproduce PPX1 is attributed to depressed levels of rpoS expression. Since rpoS is a central element in a regulatory network that governs the expression of stationary-phase-induced genes, poly(P) affects the expression of many genes through controlling rpoS expression. Furthermore, poly(P) is also involved in expression of other stress-inducible genes that are not directly regulated by rpoS. The second subject includes the application of novel functions of PPK for nucleoside triphosphate (NTP) regeneration. Recently E. coli PPK has been found to catalyze the kination of not only ADP but also other nucleoside diphosphates using poly(P) as a phospho-donor, yielding NTPs. This nucleoside diphosphate kinase-like activity of PPK was confirmed to be available for NTP regeneration essential for enzymatic oligosaccharide synthesis using the sugar nucleotide cycling method. PPK has also been found to express a poly(P):AMP phosphotransferase activity by coupling with adenylate kinase (ADK) in E. coli. The ATP-regeneration system consisting of ADK, PPK, and poly(P) was shown to be promising for practical utilization of poly(P) as ATP substitute.